A genome for Cissus illustrates features underlying its evolutionary success in dry savannas. Issue 1 (13th September 2022) - Xin, Haiping; Wang, Yi; Li, Qingyun; Wan, Tao; Hou, Yujun; Liu, Yuanshuang; Gichuki, Duncan Kiragu; Zhou, Huimin; Zhu, Zhenfei; Xu, Chen; Zhou, Yadong; Liu, Zhiming; et al.
Abstract: Cissus is the largest genus in Vitaceae and is mainly distributed in the tropics and subtropics. Crassulacean acid metabolism (CAM), a photosynthetic adaptation to the occurrence of succulent leaves or stems, indicates that convergent evolution occurred in response to drought stress during species radiation. Here we provide the chromosomal level assembly of Cissus rotundifolia (an endemic species in Eastern Africa) and a genome-wide comparison with grape to understand genome divergence within an ancient eudicot family. Extensive transcriptome data were produced to illustrate the genetics underpinning C. rotundifolia 's ecological adaption to seasonal aridity. The modern karyotype and smaller genome of C. rotundifolia ( n = 12, 350.69 Mb/1C), which lack further whole-genome duplication, were mainly derived from gross chromosomal rearrangements such as fusions and segmental duplications, and were sculpted by a very recent burst of retrotransposon activity. Bias in local gene amplification contributed to its remarkable functional divergence from grape, and the specific proliferated genes associated with abiotic and biotic responses (e.g. HSP-20, NBS-LRR ) enabled C. rotundifolia to survive in a hostile environment. Reorganization of existing enzymes of CAM characterized as diurnal expression patterns of relevant genes further confer the ability to thrive in dry savannas.